Bandichan, Surchandarja, Usbekistan: Die Arbeiten der Jahre 2012 und 2013 - Boroffka, Nikolaus (e-Forschungsberichte des DAI, 2023)
The Bandikhan settlement oasis offers „pure“ sites for various times from the Late Bronze Age to the Early Medieval period. Since they are not disturbed by later activity they allow good definition of cultural phenomena. Discovered in the early 1970s by E. Rtveladze, they have been re-studied by an Uzbek- German team since 2005. Majdatepa (Early Iron Age), Bektepa, Gazimullahtepa, Kindyktepa (all Iron Age), Jalangtushtepa (Antiquity) and Kakhramontepa (Early Medieval), as well as burials around Kakhramontepa and Sariband have been studied.